The survey of Malathion removal using magnetic graphene oxide nanocomposite as a novel adsorbent: thermodynamics, isotherms, and kinetic study. Issue 58 (13th December 2016) - Kalantary, Roshanak Rezaei; Azari, Ali; Esrafili, Ali; Yaghmaeian, Kamyar; Moradi, Masoud; Sharafi, Kiomars
Abstract: Malathion is a persistent organophosphorous insecticide, which is widely used in industry, agriculture, and public health. The characterization of Magnetic Graphene Oxide (MGO) was determined by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, energy dispersive X-ray, vibrating sample magnetometer, and zeta potential. The performance of the adsorbent in removing of malathion was evaluated in different operational conditions including pH, contact time, adsorbent dosage, initial adsorbate concentration, and temperature. The Langmuir and Freundlich isotherms and pseudo-first-order and pseudo-second-order models were applied to describe the adsorption process. The results showed that the maximum adsorption capacity was obtained 43.29 mg g −1 and equilibrium data fitted well with the Langmuir isotherm and kinetics of reactions obeyed the pseudo-second-order model. It was also found that the adsorption process was dependent on pH and it was spontaneous and exothermic in terms of thermodynamic studies. Desorption experiments implied that MGO has high stability (very low component leaching) and is probable that can be applied as a novel material for malathion removal from aqueous environments.